Incarnating the Missionary-Pastoral Character of the Churches in Asia - Pojol, Peter, SJ (Archīum Ateneo, 2021)
The emergence and growth of pastoral institutes in Asia manifests the missionary-pastoral trajectories that were made the center of the focus of the Church by Vatican II, echoed by the Federation of Asian Bishops’ Conferences (FABC), and reaffirmed and rejuvenated for our time by Pope Francis. The pastoral institutes of Network Pastoral Asia and Inter-Institutional Collaboration illustrate this impetus. They invite sustained reflection on and creative application of the Council's “principle of pastorality,” which carefully attends to context and faithfully expresses the “centrifugal missionary dimension” of evangelization.